Ethnic Identity and Familism Among Latino College Students: A Test of Prospective Associations. (April 2017) - Stein, Gabriela L.; Rivas-Drake, Deborah; Camacho, Tissyana C.
The present study examined the longitudinal associations among familism respect and obligations values, ethnic centrality and private regard, and ethnic self-identification. Data were drawn from a socioeconomically diverse sample of Latino students attending a predominantly White university. The selection of a White label was associated with less positive private regard, less ethnic centrality, and less strong endorsement of familism respect and obligation values at the start of the academic year compared to those students who selected a national origin label. There was a complex relationship between ethnic identity and familism values over time. Ethnic centrality supported the growth in familism respect values across time, but familism respect values also predicted later growth in ethnic private regard. Our results highlight the fact that ethnic identity processes and familial cultural values can mutually influence each other in emerging adulthood for Latinos.